Meta‐analysis of operative mortality and complications in patients from minority ethnic groups. Issue 11 (5th August 2014) - Bloo, G. J. A.; Hesselink, G. J.; Oron, A.; Emond, E. J. J. M.; Damen, J.; Dekkers, W. J. M.; Westert, G.; Wolff, A. P.; Calsbeek, H.; Wollersheim, H. C.
<x xml:space="preserve">Abstract</x> Background Insight into the effects of ethnic disparities on patients' perioperative safety is necessary for the development of tailored improvement strategies. The aim of this study was to review the literature on safety differences between patients from minority ethnic groups and those from the ethnic majority undergoing surgery. Methods PubMed, CINAHL, the Cochrane Library and Embase were searched using predefined inclusion criteria for available studies from January 1990 to January 2013. After quality assessment, the study data were organized on the basis of outcome, statistical significance and the direction of the observed effects. Relative risks for mortality were calculated. Results After screening 3105 studies, 26 studies were identified. Nine of these 26 studies showed statistically significant higher mortality rates for patients from minority ethnic groups. Meta‐analysis demonstrated a greater risk of mortality for these patients compared with patients from the Caucasian majority in studies performed both in North America (risk ratio 1·22, 95 per cent confidence interval 1·05 to 1·42) and outside (risk ratio 2·25, 1·40 to 3·62). For patients from minority groups, the length of hospital or intensive care unit stay was significantly longer in five studies, and complication rates were significantly higher in ten. Methods used to identify patient ethnicity were not described in 14 studies. Conclusion Patients from minority ethnic groups, in North America and elsewhere, have an increased risk of perioperative death and complications. More insight is needed into the causes of ethnic disparities to pursue safer perioperative care for patients of minority ethnicity.